Implementation of Ramadan Safari as a Means of Learning Islamic Preaching - Siti Muklisatun Kasanah; Anis Nabihah Binti Basri (International Journal of Islamic Pedagogical Research, 2026)
This study aims to analyze the implementation of the Ramadan Safari program as a means of Islamic da’wah learning at SMK Plus Al Mutamakkin. The research employs a qualitative descriptive approach to explore how Ramadan Safari activities are planned, implemented, and evaluated as part of the da’wah learning process. Data were collected through observation, in-depth interviews, and documentation involving school principals, Islamic education teachers, organizing committees, and students participating in the program. The findings indicate that the Ramadan Safari program functions not only as an annual religious activity but also as a contextual and experiential learning medium for Islamic da’wah. Through direct involvement in da’wah activities within the community, students gain meaningful learning experiences that enhance their understanding of Islamic teachings, internalize religious and moral values, and develop practical da’wah skills, particularly in communication and social interaction. However, the study also reveals that the planning and evaluation of da’wah learning through the Ramadan Safari program have not been systematically structured with measurable learning indicators. Despite these limitations, the program demonstrates significant potential as an effective model of contextual Islamic da’wah learning in vocational secondary education. Therefore, strengthening systematic planning and evaluation is recommended to optimize the role of the Ramadan Safari program as a sustainable Islamic da’wah learning strategy. This study contributes theoretically by enriching the concept of contextual and experiential Islamic da’wah learning, and practically offers a model for integrating community-based religious activities into structured educational programs.